Effects of vegetation patchiness on ecosystem carbon and nitrogen storage in the alpine grassland of the Qilian Mountains - Abalori, Theophilus Atio; Cao, Wenxia; Atogi-Akwoa Weobong, Conrad; Sam, Faisal Eudes; Li, Wen; Osei, Richard; Wang, Shilin (Frontiers in Environmental Science, 2022)
Vegetation patchiness is common in degraded grasslands. Vegetation patchiness enhances the spatial variability of grassland soil organic carbon and total nitrogen. Stripped vegetation patches have a great impact on ecosystem carbon (C) and nitrogen (N) storage. Using field surveys, we examined the effects of patches on ecosystem carbon and nitrogen storage of four typical alpine grass species patches. The results indicated ecosystem C, N and respiration were significantly higher in intact vegetation patches than the stripped vegetation patches. Also, stripped vegetation patches recorded higher quantities of soil gravel content than the intact patches. In Leymus secalinus and Koeleria pers species patches, soil approximately contributed about 62% and vegetation about 38% to ecosystem carbon and nitrogen storage whereas, in Stipa aliena and Leontopodium nanum species patches, close to 80% of ecosystem carbon and nitrogen were found in soil while close to 20% were stored in vegetation. Soil total phosphorus (TP), total potassium (TK), available phosphorus (AP), soil microbial biomass carbon (MBC) and soil microbial biomass nitrogen (MBN) were high in intact vegetation patches than the stripped vegetation patches. Ecosystem carbon and nitrogen were observed to have a significant correlation with soil gravel content and vegetation productivity. Stripped vegetation patches resulted in decreased plant biomass input and increased rate of soil erosion. It is our conclusion that grassland patchiness resulted in the decline of ecosystem carbon and nitrogen storage due to a reduction in vegetation input and an increase in soil erosion. Grasslands are likely to have a higher possibility of serving as C sink if the input of organic matter exceeds its output via sustainable management practices